A method for preparing a copper column

By using P123 and polyacrylamide in the electroplating solution, the problems of poor flatness and height inconsistency of copper column surfaces in copper sulfate system electroplating are solved, and the surface of copper columns is better flatness and height uniformity are achieved, and the reliability of chip interconnection is improved.

CN119162622BActive Publication Date: 2025-03-07HUAMAO ZHIXIN INTEGRATED ELECTRONICS (JIANGSU) CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411668527.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-03-07
Estimated Expiration
2044-11-21

AI Technical Summary

Technical Problem

In the prior art, when copper columns are prepared by electroplating of copper sulfate systems, there are problems such as poor surface flatness of copper columns and inconsistent height of copper columns.

Method used

An electroplating solution containing polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer (P123) and polyacrylamide is used. By cooperating with each other in the electroplating solution, the release rate of copper ions and the refinement of copper grains are controlled, and the surface flatness and height uniformity of the copper column are improved.

Benefits of technology

The flatness of the copper column surface and the uniformity of the copper column height at different positions of the chip are significantly improved. The TIR is between ±10%, and the WID is <10%, which improves the reliability of subsequent interconnections.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119162622B_ABST
    Figure CN119162622B_ABST
Patent Text Reader

Abstract

The present invention belongs to the field of semiconductors, and specifically relates to a method for preparing a copper column. In the process of electroplating a copper column on a chip wafer, the electroplating solution used in the present invention contains a polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer and polyacrylamide, which can significantly improve the flatness of the copper column surface and the uniformity of the copper column height.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of semiconductors, and in particular relates to a method for preparing a copper column. Background Art

[0002] Copper pillar bump interconnection technology is one of the key technologies for advanced packaging flip chips and has received widespread attention. The preparation process of copper pillar bumps mainly includes spin coating photoresist (such as polyimide) on silicon wafers and photoresist etching patterning, sputtering seed layer (including Ti or TiW adhesion layer and Cu electroplating seed layer on the adhesion layer, UBM), coating photoresist (PR) and photolithography of the pattern to be electroplated, electroplating of copper pillar bumps, electroplating of solder, removal of PR and UBM, and solder reflow. If it is applied to the chip packaging process of copper-copper bonding, after electroplating the copper pillar, the electroplating of solder is omitted, and the hot pressing bonding process is directly performed after removing PR and UBM.

[0003] In the copper pillar bump interconnection process, electroplating copper pillars is one of the most challenging links. For the subsequent tin solder electroplating or copper-copper bonding process, it is generally required that the top surface morphology of the copper pillar is flat and the height of the copper pillar array on the chip must be controlled within a range, otherwise the subsequent interconnection is likely to cause a short circuit. Electroplating copper pillars is essentially a process of electrochemical copper deposition. There are many systems involved in electroplating copper, including cyanide systems, pyrophosphate systems, copper sulfate systems, and copper methanesulfonate systems. Due to the differences in electrochemical reactions and microscopic reactions caused by the components of each system, each electroplating system has its own advantages and disadvantages. At present, the copper sulfate system is commonly used in industry, which generally includes copper sulfate, chloride ions, inorganic acids, and three types of additives: accelerators, inhibitors, and levelers. Through the differential adsorption of the three additive molecules on the surface of metal copper, the deposition of copper is accelerated or inhibited. The preparation of copper pillar bumps and the flatness of a copper pillar surface and the uniformity of the height of multiple copper pillars at different positions on the chip are controlled. Different types of additives have different effects on electroplated copper pillars. The electroplating system in the prior art still has defects such as the surface flatness of the electroplated copper pillars and the inconsistency of the height of the copper pillars.

[0004] Therefore, there is still a need to continue to develop a technology that improves the flatness of the copper pillar surface and the uniformity of the copper pillar height at different positions of the chip. Summary of the invention

[0005] In view of the defects of poor surface flatness and inconsistent height of copper pillars in the copper sulfate system electroplating process for preparing copper pillars in the above-mentioned prior art, the present invention provides a method for preparing copper pillars.

[0006] To achieve the above purpose, the following technical solutions are specifically included:

[0007] A method for preparing a copper column comprises the following steps:

[0008] (1) Providing chip wafer metal pads to be electroplated;

[0009] (2) subjecting the metal pads of the chip wafer to be electroplated to air plasma cleaning and acid immersion in sequence;

[0010] (3) electroplating the metal pads of the chip wafer to be electroplated after acid immersion in step (2) in an electroplating solution, and then cleaning and debonding to obtain the copper pillars;

[0011] The electroplating solution includes the following components: 100-200 g / L copper sulfate, 40-150 g / L sulfuric acid, Cl - 20-50mg / L, accelerator 10-50mg / L, polyethylene glycol 20-150mg / L, polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer 10-50mg / L, polyacrylamide 5-30mg / L, and the balance water.

[0012] In the electroplating of copper pillars, the polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer (P123) and polyacrylamide in the plating solution act as inhibitors and leveling agents respectively, and cooperate with each other to significantly improve the flatness of the copper pillar surface and the uniformity of the copper pillar height at different positions of the chip.

[0013] Preferably, the acid used in the acid leaching is a 20-80 g / L aqueous solution of sulfuric acid.

[0014] Preferably, the solvent used in the debonding is a mixed solution of tetramethylammonium hydroxide (TMAH) and DMSO, and the mass ratio of tetramethylammonium hydroxide to DMSO is 1:(0.5-3). There is photoresist on the metal pad of the chip wafer to be electroplated, and the photoresist is removed by the debonding process to expose the metallization layer.

[0015] Preferably, the polyacrylamide includes at least one of anionic polyacrylamide, cationic polyacrylamide and amphoteric polyacrylamide.

[0016] The main chain of polyacrylamide contains a large number of active amide groups, which are conducive to affinity or adsorption of many substances to form hydrogen bonds. In the electroplating system of the present invention, polyacrylamide and polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer and other substances may cooperate and cooperate with each other. On the one hand, it can synergistically control the release rate of copper ions, thereby controlling the deposition rate of copper and improving the quality of copper plating in the hole; on the other hand, it can refine the copper grains, reduce the gaps or holes of the copper column, and improve the surface flatness of the copper column. At the same time, polyacrylamide includes anionic polyacrylamide, cationic polyacrylamide, and amphoteric polyacrylamide. There are differences in the properties of the three such as molecular stress, charge, and ionicity, so that the three have different effects of flattening copper columns in the electroplating solution system. In the system of the present invention, anionic polyacrylamide is further preferred.

[0017] Preferably, the mass ratio of the polyacrylamide to the polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer is 1:(0.5-7).

[0018] Further preferably, the mass ratio of the polyacrylamide to the polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer is 1:(3-4).

[0019] The ethylene oxide group in the polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer is a hydrophilic group, and the propylene oxide group is a hydrophobic group. The whole acts as a surfactant to reduce the surface tension in the electroplating solution, improves the wettability of the electroplated copper column surface, and improves the flatness of the copper column surface. At the same time, it acts as an inhibitor to cooperate with polyacrylamide and other substances to inhibit the deposition of the copper plating layer outside the hole, and improves the flatness of the copper column surface. The copper column surface has better flatness than the mass ratio of the above polyacrylamide and the polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer.

[0020] Preferably, the polyethylene glycol includes at least one of PEG200, PEG400, PEG600, PEG800, PEG1000, PEG2000, PEG3000, PEG4000, PEG6000, PEG8000, PEG10000, and PEG20000.

[0021] Further preferably, the polyethylene glycol is a compound of PEG800 and PEG2000, and the mass ratio of PEG800 to PEG2000 is 1:(0.5-1.5).

[0022] Polyethylene glycol has the function of an inhibitor, which can cooperate with other substances to control the deposition of copper ions in the micropores, inhibit the copper plating outside the pores, and improve the quality of the copper column.

[0023] Preferably, the accelerator includes at least one of 3-mercapto-1-propanesulfonate, polydisulfide propanesulfonate, 3-mercapto-ethylsulfonate, and 3-mercapto-1-ethanesulfonic acid potassium salt. The accelerator can accelerate the deposition rate of copper ions in the micropores, reduce the defects of leak plating and plating in the micropores, and compete with other inhibitor substances for adsorption to improve the electroplating quality of the copper column.

[0024] Preferably, the electroplating is performed under the protection of an inert gas. The service life of the electroplating solution can be increased in a nitrogen inert gas atmosphere.

[0025] Preferably, the chip wafer metal pad to be electroplated includes a wafer substrate, a metal pad, an insulating layer, a metallization layer, and a photoresist in sequence; the metallization layer includes an adhesion layer and a copper seed layer, the thickness of the copper seed layer is 100-500nm, and micropores are present on the photoresist to expose the metallization layer; the diameter of the micropores is 50-150μm, the pore spacing between the micropores is 80-200μm, and the thickness of the photoresist is 10-150μm.

[0026] Preferably, the current density of the electroplating is 5-40A / dm 2 , the electroplating time is 10-60min.

[0027] A wafer comprises, from bottom to top, a wafer substrate, a metal pad, an insulating layer and a metallization layer, and a copper pillar made on the metallization layer by the copper pillar preparation method. The copper pillar on the wafer made by the method of the present invention has excellent surface flatness and coplanarity, so that the wafer has better reliability in subsequent interconnection.

[0028] Compared with the prior art, the present invention has the following beneficial effects: in the process of electroplating copper pillars, the polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer (P123) and polyacrylamide contained in the electroplating solution can significantly improve the flatness of the copper pillar surface and the uniformity of the copper pillar height, wherein TIR is between ±10% and WID<10%. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 A schematic diagram of a chip wafer metal pad to be electroplated with a copper pillar;

[0030] Figure 2 Schematic diagram of copper pillars after electroplating;

[0031] Figure 1 and Figure 2 In the figure, 1-wafer substrate, 2-metal pad, 3-insulating layer, 4-metallization layer, 4-1-adhesion layer, 4-2-Cu seed layer, 5-copper pillar, 6-photoresist, 7-microhole on the photoresist. DETAILED DESCRIPTION

[0032] In order to better illustrate the purpose, technical scheme and advantages of the present invention, the present invention will be further described below through specific examples. The test methods used in the examples and / or comparative examples are conventional methods unless otherwise specified; the materials, reagents, etc. used can be obtained from commercial channels unless otherwise specified.

[0033] Example 1

[0034] A method for preparing a copper column comprises the following steps:

[0035] (1) Provide a chip wafer metal pad (commercially available, manufactured by Guangdong Fozhixin Microelectronics Technology Research Co., Ltd.) for electroplating copper pillars. The chip wafer metal pad includes, from bottom to top, a wafer substrate 1, a metal pad 2, an insulating layer 3, a metallization layer 4, a photoresist 6, and microholes 7 on the photoresist. The structural schematic diagram can be referred to as Figure 1 and attached Figure 2 ;

[0036] The thickness of the photoresist 6 is 50 μm (see attached Figure 1 C in the figure), the diameter of the micropore 7 thereon is 80 μm (see Appendix Figure 1 The spacing between micropores is 150 μm (see Appendix Figure 1 B in );

[0037] The metallization layer 4 includes an adhesion layer 4-1 and a Cu seed layer 4-2; wherein the adhesion layer 4-1 can enhance the adhesion between metals, so that the upper and lower layers are firmly adhered and not easy to peel off; the Cu seed layer 4-2 is composed of a 100nm Ti barrier layer and a 300nm copper seed layer sputtered by PVD technology, and the Cu seed layer 4-2 is sputtered on the surface of the adhesion layer 4-1, so that the subsequent copper electroplating process can be realized;

[0038] (2) Use air plasma to clean the metal pads of the chip wafer for 10-30 seconds, then acid dip it in a 50g / L sulfuric acid solution and remove bubbles by shaking. Air plasma cleaning can remove impurities and bubbles at the bottom of the micropores and increase the wettability of subsequent electroplating.

[0039] (3) Under the protection of nitrogen atmosphere, the copper column is placed in the electroplating solution for electroplating. The electroplating current density is 10ASD (1ASD = A / dm 2 ), the electroplating time is 40min, the electroplating temperature is 30℃, and the speed during the electroplating process is 30rpm;

[0040] The components of the electroplating solution are: copper sulfate pentahydrate 150g / L, sulfuric acid 100g / L, Cl -35 mg / L, sodium 3-mercapto-1-propanesulfonate (MPS) 15 mg / L, polyethylene glycol 800 (PEG800, purchased from Merck) 50 mg / L, P123 30 mg / L (purchased from Sigma-Aldrich), anionic polyacrylamide (purchased from Foshan Jianghe Chemical) 10 mg / L, solvent water;

[0041] (4) After electroplating, the substrate is washed with water and then the photoresist is removed with a mixed solution of TMAH and DMSO (mass ratio is 1:1) to expose the deposited copper pillars.

[0042] Example 2

[0043] The difference between this embodiment and embodiment 1 is that the anionic polyacrylamide in the electroplating solution of this embodiment is replaced by an equal amount of cationic polyacrylamide (purchased from Foshan Jianghe Chemical Industry). The detailed process is as follows:

[0044] (1) Provide a chip wafer metal pad (commercially available, manufactured by Guangdong Fozhixin Microelectronics Technology Research Co., Ltd.) for electroplating copper pillars. The chip wafer metal pad includes, from bottom to top, a wafer substrate 1, a metal pad 2, an insulating layer 3, a metallization layer 4, a photoresist 6, and microholes 7 on the photoresist. The structural schematic diagram can be referred to as Figure 1 and attached Figure 2 ;

[0045] The thickness of the photoresist 6 is 50 μm (see attached Figure 1 C in the figure), the diameter of the micropore 7 thereon is 80 μm (see Appendix Figure 1 The spacing between micropores is 150 μm (see Appendix Figure 1 B in );

[0046] The metallization layer 4 includes an adhesion layer 4-1 and a Cu seed layer 4-2; wherein the adhesion layer 4-1 can enhance the adhesion between metals, so that the upper and lower layers are firmly adhered and not easy to peel off; the Cu seed layer 4-2 is composed of a 100nm Ti barrier layer and a 300nm copper seed layer sputtered by PVD technology, and the Cu seed layer 4-2 is sputtered on the surface of the adhesion layer 4-1, so that the subsequent copper electroplating process can be realized;

[0047] (2) Use air plasma to clean the metal pads of the chip wafer for 10-30 seconds, then acid dip it in a 50g / L sulfuric acid solution and remove bubbles by shaking. Air plasma cleaning can remove impurities and bubbles at the bottom of the micropores and increase the wettability of subsequent electroplating.

[0048] (3) Under the protection of nitrogen atmosphere, the copper column is placed in the electroplating solution for electroplating. The electroplating current density is 10ASD (1ASD = A / dm 2), the electroplating time is 40min, the electroplating temperature is 30℃, and the speed is 30rpm during the electroplating process;

[0049] The components of the electroplating solution are: copper sulfate pentahydrate 150g / L, sulfuric acid 100g / L, Cl - 35 mg / L, sodium 3-mercapto-1-propanesulfonate (MPS) 15 mg / L, polyethylene glycol 800 (PEG800, purchased from Merck) 50 mg / L, P123 30 mg / L (purchased from Sigma-Aldrich), cationic polyacrylamide (purchased from Foshan Jianghe Chemical) 10 mg / L, solvent water;

[0050] (4) After electroplating, the substrate is washed with water and then the photoresist is removed with a mixed solution of TMAH and DMSO (mass ratio is 1:1) to expose the deposited copper pillars.

[0051] Example 3

[0052] The difference between this embodiment and embodiment 1 is that anionic polyacrylamide is replaced with an equal amount of zwitterionic polyacrylamide in the electroplating solution of this embodiment. The detailed process is as follows:

[0053] (1) Provide a chip wafer metal pad (commercially available, manufactured by Guangdong Fozhixin Microelectronics Technology Research Co., Ltd.) for electroplating copper pillars. The chip wafer metal pad includes, from bottom to top, a wafer substrate 1, a metal pad 2, an insulating layer 3, a metallization layer 4, a photoresist 6, and microholes 7 on the photoresist. The structural schematic diagram can be referred to as Figure 1 and attached Figure 2 ;

[0054] The thickness of the photoresist 6 is 50 μm (see attached Figure 1 C in the figure), the diameter of the micropore 7 thereon is 80 μm (see Appendix Figure 1 The spacing between micropores is 150 μm (see Appendix Figure 1 B in );

[0055] The metallization layer 4 includes an adhesion layer 4-1 and a Cu seed layer 4-2; wherein the adhesion layer 4-1 can enhance the adhesion between metals, so that the upper and lower layers are firmly adhered and not easy to peel off; the Cu seed layer 4-2 is composed of a 100nm Ti barrier layer and a 300nm copper seed layer sputtered by PVD technology, and the Cu seed layer 4-2 is sputtered on the surface of the adhesion layer 4-1, so that the subsequent copper electroplating process can be realized;

[0056] (2) Use air plasma to clean the metal pads of the chip wafer for 10-30 seconds, then acid dip it in a 50g / L sulfuric acid solution and remove bubbles by shaking. Air plasma cleaning can remove impurities and bubbles at the bottom of the micropores and increase the wettability of subsequent electroplating.

[0057] (3) Under the protection of nitrogen atmosphere, the copper column is placed in the electroplating solution for electroplating. The electroplating current density is 10ASD (1ASD = A / dm 2 ), the electroplating time is 40min, the electroplating temperature is 30℃, and the speed during the electroplating process is 30rpm;

[0058] The components of the electroplating solution are: copper sulfate pentahydrate 150g / L, sulfuric acid 100g / L, Cl - 35mg / L, 3-mercapto-1-propanesulfonate sodium (MPS) 15mg / L, polyethylene glycol 800 (PEG800, purchased from Merck) 50mg / L, P123 30mg / L (purchased from Sigma-Aldrich), zwitterionic polyacrylamide (purchased from Gongyi Mingrui Water Purification Materials Co., Ltd.) 10mg / L, solvent water;

[0059] (4) After electroplating, the substrate is washed with water and then the photoresist is removed with a mixed solution of TMAH and DMSO (mass ratio is 1:1) to expose the deposited copper pillars.

[0060] Example 4

[0061] The difference between this embodiment and embodiment 1 is that the mass ratio of polyacrylamide to P123 in the electroplating solution of this embodiment is 1:0.5, that is, polyacrylamide 27 mg / L, P123 13 mg / L. The detailed process is as follows:

[0062] (1) Provide a chip wafer metal pad (commercially available, manufactured by Guangdong Fozhixin Microelectronics Technology Research Co., Ltd.) for electroplating copper pillars. The chip wafer metal pad includes, from bottom to top, a wafer substrate 1, a metal pad 2, an insulating layer 3, a metallization layer 4, a photoresist 6, and microholes 7 on the photoresist. The structural schematic diagram can be referred to as Figure 1 and attached Figure 2 ;

[0063] The thickness of the photoresist 6 is 50 μm (see attached Figure 1 C in the figure), the diameter of the micropore 7 thereon is 80 μm (see Appendix Figure 1 The spacing between micropores is 150 μm (see Appendix Figure 1 B in );

[0064] The metallization layer 4 includes an adhesion layer 4-1 and a Cu seed layer 4-2; wherein the adhesion layer 4-1 can enhance the adhesion between metals, so that the upper and lower layers are firmly adhered and not easy to peel off; the Cu seed layer 4-2 is composed of a 100nm Ti barrier layer and a 300nm copper seed layer sputtered by PVD technology, and the Cu seed layer 4-2 is sputtered on the surface of the adhesion layer 4-1, so that the subsequent copper electroplating process can be realized;

[0065] (2) Use air plasma to clean the metal pads of the chip wafer for 10-30 seconds, then acid dip it in a 50g / L sulfuric acid solution and remove bubbles by shaking. Air plasma cleaning can remove impurities and bubbles at the bottom of the micropores and increase the wettability of subsequent electroplating.

[0066] (3) Under the protection of nitrogen atmosphere, the copper column is placed in the electroplating solution for electroplating. The electroplating current density is 10ASD (1ASD = A / dm 2 ), the electroplating time is 40min, the electroplating temperature is 30℃, and the speed during the electroplating process is 30rpm;

[0067] The components of the electroplating solution are: copper sulfate pentahydrate 150g / L, sulfuric acid 100g / L, Cl - 35 mg / L, sodium 3-mercapto-1-propanesulfonate (MPS) 15 mg / L, polyethylene glycol 800 (PEG800, purchased from Merck) 50 mg / L, P123 13 mg / L (purchased from Sigma-Aldrich), anionic polyacrylamide (purchased from Foshan Jianghe Chemical) 27 mg / L, solvent water;

[0068] (4) After electroplating, the surface was washed with water, and then the photoresist was removed with a mixed solution of TMAH and DMSO (mass ratio of 1:1) to expose the deposited copper pillars.

[0069] Example 5

[0070] The difference between this embodiment and embodiment 1 is that the mass ratio of polyacrylamide and P123 in the electroplating solution of this embodiment is 1:1.5, that is, polyacrylamide 16 mg / L, P123 24 mg / L, and the detailed process is as follows:

[0071] (1) Provide a chip wafer metal pad (commercially available, manufactured by Guangdong Fozhixin Microelectronics Technology Research Co., Ltd.) for electroplating copper pillars. The chip wafer metal pad includes, from bottom to top, a wafer substrate 1, a metal pad 2, an insulating layer 3, a metallization layer 4, a photoresist 6, and microholes 7 on the photoresist. The structural schematic diagram can be referred to as Figure 1 and attached Figure 2 ;

[0072] The thickness of the photoresist 6 is 50 μm (see attached Figure 1 C in the figure), the diameter of the micropore 7 thereon is 80 μm (see Appendix Figure 1 The spacing between micropores is 150 μm (see Appendix Figure 1 B in );

[0073] The metallization layer 4 includes an adhesion layer 4-1 and a Cu seed layer 4-2; wherein the adhesion layer 4-1 can enhance the adhesion between metals, so that the upper and lower layers are firmly adhered and not easy to peel off; the Cu seed layer 4-2 is composed of a 100nm Ti barrier layer and a 300nm copper seed layer sputtered by PVD technology, and the Cu seed layer 4-2 is sputtered on the surface of the adhesion layer 4-1, so that the subsequent copper electroplating process can be realized;

[0074] (2) Use air plasma to clean the metal pads of the chip wafer for 10-30 seconds, then acid dip it in a 50g / L sulfuric acid solution and remove bubbles by shaking. Air plasma cleaning can remove impurities and bubbles at the bottom of the micropores and increase the wettability of subsequent electroplating.

[0075] (3) Under the protection of nitrogen atmosphere, the copper column is placed in the electroplating solution for electroplating. The electroplating current density is 10ASD (1ASD = A / dm 2 ), the electroplating time is 40min, the electroplating temperature is 30℃, and the speed during the electroplating process is 30rpm;

[0076] The components of the electroplating solution are: copper sulfate pentahydrate 150g / L, sulfuric acid 100g / L, Cl - 35 mg / L, sodium 3-mercapto-1-propanesulfonate (MPS) 15 mg / L, polyethylene glycol 800 (PEG800, purchased from Merck) 50 mg / L, P123 24 mg / L (purchased from Sigma-Aldrich), anionic polyacrylamide (purchased from Foshan Jianghe Chemical) 16 mg / L, solvent water;

[0077] (4) After electroplating, the substrate is washed with water and then the photoresist is removed with a mixed solution of TMAH and DMSO (mass ratio is 1:1) to expose the deposited copper pillars.

[0078] Example 6

[0079] The difference between this embodiment and embodiment 1 is that the mass ratio of polyacrylamide to P123 in the electroplating solution of this embodiment is 1:4, that is, polyacrylamide 8 mg / L, P123 32 mg / L. The detailed process is as follows:

[0080] (1) Provide a chip wafer metal pad (commercially available, manufactured by Guangdong Fozhixin Microelectronics Technology Research Co., Ltd.) for electroplating copper pillars. The chip wafer metal pad includes, from bottom to top, a wafer substrate 1, a metal pad 2, an insulating layer 3, a metallization layer 4, a photoresist 6, and microholes 7 on the photoresist. The structural schematic diagram can be referred to as Figure 1 and attached Figure 2 ;

[0081] The thickness of the photoresist 6 is 50 μm (see attached Figure 1C in the figure), the diameter of the micropore 7 thereon is 80 μm (see Appendix Figure 1 The spacing between micropores is 150 μm (see Appendix Figure 1 B in );

[0082] The metallization layer 4 includes an adhesion layer 4-1 and a Cu seed layer 4-2; wherein the adhesion layer 4-1 can enhance the adhesion between metals, so that the upper and lower layers are firmly adhered and not easy to peel off; the Cu seed layer 4-2 is composed of a 100nm Ti barrier layer and a 300nm copper seed layer sputtered by PVD technology, and the Cu seed layer 4-2 is sputtered on the surface of the adhesion layer 4-1, so that the subsequent copper electroplating process can be realized;

[0083] (2) Use air plasma to clean the metal pads of the chip wafer for 10-30 seconds, then acid dip it in a 50g / L sulfuric acid solution and remove bubbles by shaking. Air plasma cleaning can remove impurities and bubbles at the bottom of the micropores and increase the wettability of subsequent electroplating.

[0084] (3) Under the protection of nitrogen atmosphere, the copper column is placed in the electroplating solution for electroplating. The electroplating current density is 10ASD (1ASD = A / dm 2 ), the electroplating time is 40min, the electroplating temperature is 30℃, and the speed during the electroplating process is 30rpm;

[0085] The components of the electroplating solution are: copper sulfate pentahydrate 150g / L, sulfuric acid 100g / L, Cl - 35mg / L, sodium 3-mercapto-1-propanesulfonate (MPS) 15mg / L, polyethylene glycol 800 (PEG800, purchased from Merck) 50mg / L, P123 32mg / L (purchased from Sigma-Aldrich), anionic polyacrylamide (purchased from Foshan Jianghe Chemical) 8mg / L, solvent water;

[0086] (4) After electroplating, the substrate is washed with water and then the photoresist is removed with a mixed solution of TMAH and DMSO (mass ratio is 1:1) to expose the deposited copper pillars.

[0087] Example 7

[0088] The difference between this embodiment and embodiment 1 is that the mass ratio of polyacrylamide to P123 in the electroplating solution of this embodiment is 1:7, that is, polyacrylamide 5 mg / L, P123 35 mg / L. The detailed process is as follows:

[0089] (1) Provide a chip wafer metal pad (commercially available, manufactured by Guangdong Fozhixin Microelectronics Technology Research Co., Ltd.) for electroplating copper pillars. The chip wafer metal pad includes, from bottom to top, a wafer substrate 1, a metal pad 2, an insulating layer 3, a metallization layer 4, a photoresist 6, and microholes 7 on the photoresist. The structural schematic diagram can be referred to as Figure 1 and attached Figure 2 ;

[0090] The thickness of the photoresist 6 is 50 μm (see attached Figure 1 C in the figure), the diameter of the micropore 7 thereon is 80 μm (see Appendix Figure 1 The spacing between micropores is 150 μm (see Appendix Figure 1 B in );

[0091] The metallization layer 4 includes an adhesion layer 4-1 and a Cu seed layer 4-2; wherein the adhesion layer 4-1 can enhance the adhesion between metals, so that the upper and lower layers are firmly adhered and not easy to peel off; the Cu seed layer 4-2 is composed of a 100nm Ti barrier layer and a 300nm copper seed layer sputtered by PVD technology, and the Cu seed layer 4-2 is sputtered on the surface of the adhesion layer 4-1, so that the subsequent copper electroplating process can be realized;

[0092] (2) Use air plasma to clean the metal pads of the chip wafer for 10-30 seconds, then acid dip it in a 50g / L sulfuric acid solution and remove bubbles by shaking. Air plasma cleaning can remove impurities and bubbles at the bottom of the micropores and increase the wettability of subsequent electroplating.

[0093] (3) Under the protection of nitrogen atmosphere, the copper column is placed in the electroplating solution for electroplating. The electroplating current density is 10ASD (1ASD = A / dm 2 ), the electroplating time is 40min, the electroplating temperature is 30℃, and the speed during the electroplating process is 30rpm;

[0094] The components of the electroplating solution are: copper sulfate pentahydrate 150g / L, sulfuric acid 100g / L, Cl - 35 mg / L, sodium 3-mercapto-1-propanesulfonate (MPS) 15 mg / L, polyethylene glycol 800 (PEG800, purchased from Merck) 50 mg / L, P123 35 mg / L (purchased from Sigma-Aldrich), anionic polyacrylamide (purchased from Foshan Jianghe Chemical) 5 mg / L, solvent water;

[0095] (4) After electroplating, the substrate is washed with water and then the photoresist is removed with a mixed solution of TMAH and DMSO (mass ratio is 1:1) to expose the deposited copper pillars.

[0096] Example 8

[0097] The difference between this embodiment and embodiment 1 is that PEG800 is replaced by PEG2000 in the electroplating solution of this embodiment. The detailed process is as follows:

[0098] (1) Provide a chip wafer metal pad (commercially available, manufactured by Guangdong Fozhixin Microelectronics Technology Research Co., Ltd.) for electroplating copper pillars. The chip wafer metal pad includes, from bottom to top, a wafer substrate 1, a metal pad 2, an insulating layer 3, a metallization layer 4, a photoresist 6, and microholes 7 on the photoresist. The structural schematic diagram can be referred to as Figure 1 and attached Figure 2 ;

[0099] The thickness of the photoresist 6 is 50 μm (see attached Figure 1 C in the figure), the diameter of the micropore 7 thereon is 80 μm (see Appendix Figure 1 The spacing between micropores is 150 μm (see Appendix Figure 1 B in );

[0100] The metallization layer 4 includes an adhesion layer 4-1 and a Cu seed layer 4-2; wherein the adhesion layer 4-1 can enhance the adhesion between metals, so that the upper and lower layers are firmly adhered and not easy to peel off; the Cu seed layer 4-2 is composed of a 100nm Ti barrier layer and a 300nm copper seed layer sputtered by PVD technology, and the Cu seed layer 4-2 is sputtered on the surface of the adhesion layer 4-1, so that the subsequent copper electroplating process can be realized;

[0101] (2) Use air plasma to clean the metal pads of the chip wafer for 10-30 seconds, then acid dip it in a 50g / L sulfuric acid solution and remove bubbles by shaking. Air plasma cleaning can remove impurities and bubbles at the bottom of the micropores and increase the wettability of subsequent electroplating.

[0102] (3) Under the protection of nitrogen atmosphere, the copper column is placed in the electroplating solution for electroplating. The electroplating current density is 10ASD (1ASD = A / dm 2 ), the electroplating time is 40min, the electroplating temperature is 30℃, and the speed during the electroplating process is 30rpm;

[0103] The components of the electroplating solution are: copper sulfate pentahydrate 150g / L, sulfuric acid 100g / L, Cl - 35mg / L, 3-mercapto-1-propanesulfonate sodium (MPS) 15mg / L, PEG2000 (purchased from MedChemExpress) 50mg / L, P123 30mg / L (purchased from Sigma-Aldrich), anionic polyacrylamide (purchased from Foshan Jianghe Chemical) 10mg / L, solvent water;

[0104] (4) After electroplating, the substrate is washed with water and then the photoresist is removed with a mixed solution of TMAH and DMSO (mass ratio is 1:1) to expose the deposited copper pillars.

[0105] Example 9

[0106] The difference between this embodiment and embodiment 1 is that PEG2000 is added to the electroplating solution of this embodiment, and the mass ratio of PEG800 to PEG2000 is 1:0.5, that is, PEG800 33 mg / L, PEG2000 17 mg / L. The detailed process is as follows:

[0107] (1) Provide a chip wafer metal pad (commercially available, manufactured by Guangdong Fozhixin Microelectronics Technology Research Co., Ltd.) for electroplating copper pillars. The chip wafer metal pad includes, from bottom to top, a wafer substrate 1, a metal pad 2, an insulating layer 3, a metallization layer 4, a photoresist 6, and microholes 7 on the photoresist. The structural schematic diagram can be referred to as Figure 1 and attached Figure 2 ;

[0108] The thickness of the photoresist 6 is 50 μm (see attached Figure 1 C in the figure), the diameter of the micropore 7 thereon is 80 μm (see Appendix Figure 1 The spacing between micropores is 150 μm (see Appendix Figure 1 B in );

[0109] The metallization layer 4 includes an adhesion layer 4-1 and a Cu seed layer 4-2; wherein the adhesion layer 4-1 can enhance the adhesion between metals, so that the upper and lower layers are firmly adhered and not easy to peel off; the Cu seed layer 4-2 is composed of a 100nm Ti barrier layer and a 300nm copper seed layer sputtered by PVD technology, and the Cu seed layer 4-2 is sputtered on the surface of the adhesion layer 4-1, so that the subsequent copper electroplating process can be realized;

[0110] (2) Use air plasma to clean the metal pads of the chip wafer for 10-30 seconds, then acid dip it in a 50g / L sulfuric acid solution and remove bubbles by shaking. Air plasma cleaning can remove impurities and bubbles at the bottom of the micropores and increase the wettability of subsequent electroplating.

[0111] (3) Under the protection of nitrogen atmosphere, the copper column is placed in the electroplating solution for electroplating. The electroplating current density is 10ASD (1ASD = A / dm 2 ), the electroplating time is 40min, the electroplating temperature is 30℃, and the speed during the electroplating process is 30rpm;

[0112] The components of the electroplating solution are: copper sulfate pentahydrate 150g / L, sulfuric acid 100g / L, Cl - 35mg / L, 3-mercapto-1-propanesulfonate sodium (MPS) 15mg / L, PEG800 33mg / L, PEG2000 17mg / L, P123 30mg / L (purchased from Sigma-Aldrich), anionic polyacrylamide (purchased from Foshan Jianghe Chemical) 10mg / L, solvent water;

[0113] (4) After electroplating, the substrate is washed with water and then the photoresist is removed with a mixed solution of TMAH and DMSO (mass ratio is 1:1) to expose the deposited copper pillars.

[0114] Example 10

[0115] The difference between this embodiment and embodiment 1 is that PEG2000 is added to the electroplating solution of this embodiment, and the mass ratio of PEG800 to PEG2000 is 1:1, that is, PEG800 25 mg / L, PEG2000 25 mg / L. The detailed process is as follows:

[0116] (1) Provide a chip wafer metal pad (commercially available, manufactured by Guangdong Fozhixin Microelectronics Technology Research Co., Ltd.) for electroplating copper pillars. The chip wafer metal pad includes, from bottom to top, a wafer substrate 1, a metal pad 2, an insulating layer 3, a metallization layer 4, a photoresist 6, and microholes 7 on the photoresist. The structural schematic diagram can be referred to as Figure 1 and attached Figure 2 ;

[0117] The thickness of the photoresist 6 is 50 μm (see attached Figure 1 C in the figure), the diameter of the micropore 7 thereon is 80 μm (see Appendix Figure 1 The spacing between micropores is 150 μm (see Appendix Figure 1 B in );

[0118] The metallization layer 4 includes an adhesion layer 4-1 and a Cu seed layer 4-2; wherein the adhesion layer 4-1 can enhance the adhesion between metals, so that the upper and lower layers are firmly adhered and not easy to peel off; the Cu seed layer 4-2 is composed of a 100nm Ti barrier layer and a 300nm copper seed layer sputtered by PVD technology, and the Cu seed layer 4-2 is sputtered on the surface of the adhesion layer 4-1, so that the subsequent copper electroplating process can be realized;

[0119] (2) Use air plasma to clean the metal pads of the chip wafer for 10-30 seconds, then acid dip it in a 50g / L sulfuric acid solution and remove bubbles by shaking. Air plasma cleaning can remove impurities and bubbles at the bottom of the micropores and increase the wettability of subsequent electroplating.

[0120] (3) Under the protection of nitrogen atmosphere, the copper column is placed in the electroplating solution for electroplating. The electroplating current density is 10ASD (1ASD = A / dm 2 ), the electroplating time is 40min, the electroplating temperature is 30℃, and the speed during the electroplating process is 30rpm;

[0121] The components of the electroplating solution are: copper sulfate pentahydrate 150g / L, sulfuric acid 100g / L, Cl -35mg / L, 3-mercapto-1-propanesulfonate sodium (MPS) 15mg / L, PEG800 25mg / L, PEG2000 25mg / L, P123 30mg / L (purchased from Sigma-Aldrich), anionic polyacrylamide (purchased from Foshan Jianghe Chemical) 10mg / L, solvent water;

[0122] (4) After electroplating, the substrate is washed with water and then the photoresist is removed with a mixed solution of TMAH and DMSO (mass ratio is 1:1) to expose the deposited copper pillars.

[0123] Embodiment 11

[0124] The difference between this embodiment and embodiment 1 is that PEG2000 is added to the electroplating solution of this embodiment, and the mass ratio of PEG800 to PEG2000 is 1:1.5, that is, PEG800 20 mg / L, PEG2000 30 mg / L. The detailed process is as follows:

[0125] (1) Provide a chip wafer metal pad (commercially available, manufactured by Guangdong Fozhixin Microelectronics Technology Research Co., Ltd.) for electroplating copper pillars. The chip wafer metal pad includes, from bottom to top, a wafer substrate 1, a metal pad 2, an insulating layer 3, a metallization layer 4, a photoresist 6, and microholes 7 on the photoresist. The structural schematic diagram can be referred to as Figure 1 and attached Figure 2 ;

[0126] The thickness of the photoresist 6 is 50 μm (see attached Figure 1 C in the figure), the diameter of the micropore 7 thereon is 80 μm (see Appendix Figure 1 The spacing between micropores is 150 μm (see Appendix Figure 1 B in );

[0127] The metallization layer 4 includes an adhesion layer 4-1 and a Cu seed layer 4-2; wherein the adhesion layer 4-1 can enhance the adhesion between metals, so that the upper and lower layers are firmly adhered and not easy to peel off; the Cu seed layer 4-2 is composed of a 100nm Ti barrier layer and a 300nm copper seed layer sputtered by PVD technology, and the Cu seed layer 4-2 is sputtered on the surface of the adhesion layer 4-1, so that the subsequent copper electroplating process can be realized;

[0128] (2) Use air plasma to clean the metal pads of the chip wafer for 10-30 seconds, then acid dip it in a 50g / L sulfuric acid solution and remove bubbles by shaking. Air plasma cleaning can remove impurities and bubbles at the bottom of the micropores and increase the wettability of subsequent electroplating.

[0129] (3) Under the protection of nitrogen atmosphere, the copper column is placed in the electroplating solution for electroplating. The electroplating current density is 10ASD (1ASD = A / dm 2), the electroplating time is 40min, the electroplating temperature is 30℃, and the speed during the electroplating process is 30rpm;

[0130] The components of the electroplating solution are: copper sulfate pentahydrate 150g / L, sulfuric acid 100g / L, Cl - 35mg / L, 3-mercapto-1-propanesulfonate sodium (MPS) 15mg / L, PEG800 20mg / L, PEG2000 30mg / L, P123 30mg / L (purchased from Sigma-Aldrich), anionic polyacrylamide (purchased from Foshan Jianghe Chemical) 10mg / L, solvent water;

[0131] (4) After electroplating, the substrate is washed with water and then the photoresist is removed with a mixed solution of TMAH and DMSO (mass ratio is 1:1) to expose the deposited copper pillars.

[0132] Example 12

[0133] The difference between this embodiment and embodiment 1 is that in this embodiment, PEG800 is replaced by PEG200 (purchased from Merck) in equal amounts in the electroplating solution. The detailed process is as follows:

[0134] (1) Provide a chip wafer metal pad (commercially available, manufactured by Guangdong Fozhixin Microelectronics Technology Research Co., Ltd.) for electroplating copper pillars. The chip wafer metal pad includes, from bottom to top, a wafer substrate 1, a metal pad 2, an insulating layer 3, a metallization layer 4, a photoresist 6, and microholes 7 on the photoresist. The structural schematic diagram can be referred to as Figure 1 and attached Figure 2 ;

[0135] The thickness of the photoresist 6 is 50 μm (see attached Figure 1 C in the figure), the diameter of the micropore 7 thereon is 80 μm (see Appendix Figure 1 The spacing between micropores is 150 μm (see Appendix Figure 1 B in );

[0136] The metallization layer 4 includes an adhesion layer 4-1 and a Cu seed layer 4-2; wherein the adhesion layer 4-1 can enhance the adhesion between metals, so that the upper and lower layers are firmly adhered and not easy to peel off; the Cu seed layer 4-2 is composed of a 100nm Ti barrier layer and a 300nm copper seed layer sputtered by PVD technology, and the Cu seed layer 4-2 is sputtered on the surface of the adhesion layer 4-1, so that the subsequent copper electroplating process can be realized;

[0137] (2) Use air plasma to clean the metal pads of the chip wafer for 10-30 seconds, then acid dip it in a 50g / L sulfuric acid solution and remove bubbles by shaking. Air plasma cleaning can remove impurities and bubbles at the bottom of the micropores and increase the wettability of subsequent electroplating.

[0138] (3) Under the protection of nitrogen atmosphere, the copper column is placed in the electroplating solution for electroplating. The electroplating current density is 10ASD (1ASD = A / dm 2 ), the electroplating time is 40min, the electroplating temperature is 30℃, and the speed during the electroplating process is 30rpm;

[0139] The components of the electroplating solution are: copper sulfate pentahydrate 150g / L, sulfuric acid 100g / L, Cl - 35mg / L, 3-mercapto-1-propanesulfonate sodium (MPS) 15mg / L, PEG200 (purchased from Merck) 50mg / L, P123 30mg / L (purchased from Sigma-Aldrich), anionic polyacrylamide (purchased from Foshan Jianghe Chemical) 10mg / L, solvent water;

[0140] (4) After electroplating, the substrate is washed with water and then the photoresist is removed with a mixed solution of TMAH and DMSO (mass ratio is 1:1) to expose the deposited copper pillars.

[0141] Example 13

[0142] The difference between this embodiment and embodiment 1 is that an equal amount of sodium polydisulfide propane sulfonate is used in the electroplating solution of this embodiment. The detailed process is as follows:

[0143] (1) Provide a chip wafer metal pad (commercially available, manufactured by Guangdong Fozhixin Microelectronics Technology Research Co., Ltd.) for electroplating copper pillars. The chip wafer metal pad includes, from bottom to top, a wafer substrate 1, a metal pad 2, an insulating layer 3, a metallization layer 4, a photoresist 6, and microholes 7 on the photoresist. The structural schematic diagram can be referred to as Figure 1 and attached Figure 2 ;

[0144] The thickness of the photoresist 6 is 50 μm (see attached Figure 1 C in the figure), the diameter of the micropore 7 thereon is 80 μm (see Appendix Figure 1 The spacing between micropores is 150 μm (see Appendix Figure 1 B in );

[0145] The metallization layer 4 includes an adhesion layer 4-1 and a Cu seed layer 4-2; wherein the adhesion layer 4-1 can enhance the adhesion between metals, so that the upper and lower layers are firmly adhered and not easy to peel off; the Cu seed layer 4-2 is composed of a 100nm Ti barrier layer and a 300nm copper seed layer sputtered by PVD technology, and the Cu seed layer 4-2 is sputtered on the surface of the adhesion layer 4-1, so that the subsequent copper electroplating process can be realized;

[0146] (2) Use air plasma to clean the metal pads of the chip wafer for 10-30 seconds, then acid dip it in a 50g / L sulfuric acid solution and remove bubbles by shaking. Air plasma cleaning can remove impurities and bubbles at the bottom of the micropores and increase the wettability of subsequent electroplating.

[0147] (3) Under the protection of nitrogen atmosphere, the copper column is placed in the electroplating solution for electroplating. The electroplating current density is 10ASD (1ASD = A / dm 2 ), the electroplating time is 40min, the electroplating temperature is 30℃, and the speed during the electroplating process is 30rpm;

[0148] The components of the electroplating solution are: copper sulfate pentahydrate 150g / L, sulfuric acid 100g / L, Cl - 35 mg / L, sodium polydisulfide bispropane sulfonate 15 mg / L, polyethylene glycol 800 (PEG800, purchased from Merck) 50 mg / L, P123 30 mg / L (purchased from Sigma-Aldrich), anionic polyacrylamide (purchased from Foshan Jianghe Chemical) 10 mg / L, solvent water;

[0149] (4) After electroplating, the substrate is washed with water and then the photoresist is removed with a mixed solution of TMAH and DMSO (mass ratio is 1:1) to expose the deposited copper pillars.

[0150] Comparative Example 1

[0151] The difference between this comparative example and Example 1 is that anionic polyacrylamide is not added to the electroplating solution of this comparative example.

[0152] Comparative Example 2

[0153] The difference between this comparative example and Example 1 is that P123 is not added to the electroplating solution of this comparative example.

[0154] Comparative Example 3

[0155] The difference between this comparative example and Example 1 is that P123 and anionic polyacrylamide are not added to the electroplating solution of this comparative example.

[0156] Comparative Example 4

[0157] The difference between this comparative example and Example 1 is that the concentration of anionic polyacrylamide in the electroplating solution of this comparative example is 1 mg / L.

[0158] Comparative Example 5

[0159] The difference between this comparative example and Example 1 is that the concentration of anionic polyacrylamide in the electroplating solution of this comparative example is 40 mg / L.

[0160] Comparative Example 6

[0161] The difference between this comparative example and Example 1 is that the concentration of P123 in the electroplating solution of this comparative example is 5 mg / L.

[0162] Comparative Example 7

[0163] The difference between this comparative example and Example 1 is that the concentration of P123 in the electroplating solution of this comparative example is 60 mg / L.

[0164] The obtained copper pillars are inspected using AOI (Automated Optical Inspection), and the inspection indicators are the qualified rate of defects such as holes and gaps and the qualified rate of coplanarity.

[0165] Coplanarity is usually expressed by Total Indicated Runout (TIR) ​​and Within-die Co-planarity / Uniformity (WID) to indicate the surface flatness and height uniformity of the copper pillar, respectively. The TIR value indicates the microscopic flatness of the copper pillar bump. The TIR of the convex copper pillar is a positive value, and the TIR of the concave copper pillar is a negative value. The absolute value of TIR is used in the following Table 1. The smaller the absolute value of TIR, the better the surface flatness of the copper pillar. The WID value indicates the macroscopic uniformity of the copper pillar bump. The larger the WID value, the greater the height difference of the copper pillars on the die. Conversely, the smaller the WID value, the more uniform the height of the copper pillars on the chip.

[0166] (1) TIR% = [H 中心高度 -H 边缘高度 ] / H 高度最大 ×100, where H 中心高度 is the height of the column measured along its mid-axis, and H 边缘高度 is the height of the column measured along its edge at the highest point on the edge; HeightMax is the height from the base of the column to its highest point on its top; HeightMax is a normalization factor.

[0167] (2) WID% = 1 / 2 × [(H 最大高度 -H 最小高度 ) / H 平均高度 ]×100, where H 最大高度 is the height of the tallest pillar of the pillar array electroplated on the substrate, measured at the highest part of the pillar; H 最小高度 is the height of the shortest pillar of the pillar array electroplated on the substrate, measured at the highest part of the pillar; H 平均高度 is the average height of all pillars electroplated on the substrate.

[0168] In order to improve the interconnection reliability of the chip, the present invention selects the allowable fluctuation range of TIR to be between ±10% and WID<10% to be qualified; the allowable fluctuation range of TIR to be between ±5% and WID<10% to be excellent.

[0169] Table 1

[0170]

[0171] It can be seen from the above-mentioned Examples 1 to 13 and Comparative Examples 1 to 7 that the present invention uses a new electroplating solution containing polyacrylamide and P123 to electroplate copper pillars, which can significantly improve the surface flatness and coplanarity of the electroplated copper pillars and improve the reliability of subsequent electrical interconnection of chip wafers.

[0172] It can be seen from Examples 1 to 3 that the polyacrylamide can be anionic polyacrylamide, cationic polyacrylamide, or amphoteric polyacrylamide. When anionic polyacrylamide is used, the surface flatness and coplanarity of the copper column are better.

[0173] It can be seen from Examples 1 and 4 to 7 that the mass ratio of polyacrylamide to P123 has an effect on the surface flatness and coplanarity of the copper pillars. The mass ratio of polyacrylamide to P123 is preferably 1:(0.5-7), and more preferably 1:(3-4).

[0174] It can be seen from Example 1 and Example 8 to Example 12 that when PEG is 800 and PEG is 2000, the surface flatness and coplanarity of the copper pillars are better.

[0175] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A method for preparing a copper column, characterized in that: The steps include: (1) Providing a chip wafer metal pad to be electroplated; the chip wafer metal pad to be electroplated includes a wafer substrate, a metal pad, an insulating layer, a metallization layer, and a photoresist in sequence; (2) subjecting the metal pads of the chip wafer to be electroplated to air plasma cleaning and acid immersion in sequence; (3) electroplating the metal pads of the chip wafer to be electroplated after acid immersion in step (2) in an electroplating solution, and then cleaning and debonding to obtain the copper pillars; The electroplating solution includes the following components: 100-200 g / L copper sulfate, 40-150 g / L sulfuric acid, Cl - 20-50mg / L, accelerator 10-50mg / L, polyethylene glycol 20-150mg / L, polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer 10-50mg / L, polyacrylamide 5-30mg / L, and the balance water.

2. The method for preparing a copper column according to claim 1, wherein The polyacrylamide includes at least one of anionic polyacrylamide, cationic polyacrylamide and amphoteric polyacrylamide.

3. The method for preparing a copper column according to claim 1, wherein The mass ratio of the polyacrylamide to the polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer is 1:(0.5-7).

4. The method for preparing a copper column according to claim 1, wherein: The polyethylene glycol includes at least one of PEG200, PEG400, PEG600, PEG800, PEG1000, PEG2000, PEG3000, PEG4000, PEG6000, PEG8000, PEG10000, and PEG20000.

5. The method for preparing a copper column according to claim 1, characterized in that: The polyethylene glycol is a compound of PEG800 and PEG2000, and the mass ratio of PEG800 to PEG2000 is 1:(0.5-1.5).

6. The method for preparing a copper column according to claim 1, characterized in that: The accelerator includes at least one of 3-mercapto-1-propane sulfonate, polydisulfide propane sulfonate, 3-mercapto-ethyl sulfonate, and 3-mercapto-1-ethane sulfonic acid potassium salt.

7. The method for preparing a copper column according to claim 1, characterized in that: The current density of the electroplating is 5-40A / dm 2 , the electroplating time is 10-60min.

8. The method for preparing a copper column according to claim 1, characterized in that: The acid used in the acid leaching is a 20-80 g / L sulfuric acid aqueous solution, the solvent used in the degumming is a mixed solution of tetramethylammonium hydroxide and DMSO; and the electroplating is carried out under the protection of an inert gas.

9. The method for preparing a copper column according to claim 1, characterized in that: The metallization layer includes an adhesion layer and a copper seed layer, the copper seed layer has a thickness of 100-500nm; micropores exist on the photoresist to expose the metallization layer; the diameter of the micropores is 50-150μm, the pore spacing between the micropores is 80-200μm, and the thickness of the photoresist is 10-150μm.

10. A wafer, characterized in that: The invention comprises a wafer substrate, a metal pad, an insulating layer and a metallization layer in sequence, and a copper column prepared on the metallization layer by the method for preparing the copper column according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Copper pillar bump interconnection structure for directional growth and preparation method of copper pillar bump interconnection structure

    CN105633038A

  • Electroplating solution and electroplating process for wafer level packaging

    CN113026067A